Role of Molecular Identification for Treatment of Highly Fatal Invasive Mucormycosis: A Meta-Analysis - Saurabh Jain; Uditkumar Agrawal; Vaibhav Agrawal; Swapnil Patond; Sanjay Agrawal (International Journal of Pharma and Bio Sciences, 2022)
India, in the last couple of years has seen surging cases of raging mucormycosis causing invasive mold infections in patients on corticosteroid therapy, those immunosuppressed and unfortunate sufferers of diabetic ketoacidosis. We all are apprised, that Rhizopus is the most common etiologic agent for Rhino-cerebral symptoms; the prevalent clinical manifestation of mucormycosis. To pinpoint Mucorales in general, we hitherto exploit the phenotypic methods like Histopathology and culture. It’s noteworthy, that both these modalities have some constraints. Their low sensitivity and specificity is attributed to common morphology of Mucorales. Momentum of molecular diagnosis, coupled with high specificity and sensitivity for species level identification, is enhanced by using semi-nested PCR with Mucorales specific primers as well as PCR with High Resolution Melting Analysis (HRMA). Liposomal Amphotericin-B has an edge over multitudes of antifungals; but for its toxicity. To analyze the role of Molecular identification for treatment of highly fatal mucormycosis, a total of 25 articles were selected for meta-analysis, the source being Pubmed and Google scholar. A Korean study of Mina Yang, M.D. et al found, species level identification is only 25 % by phenotypic method. Sarah P. Hammond et al Phenotypically identified 12 (44.44%) & Genotypically 22 (81.48%) out of 27 clinical cases of mucormycosis. This review covers an implementation of molecular methods using semi-nested PCR with Mucorales specific primers and PCR/High Resolution Met Analysis (HRMA), as routine identification for Mucorales, that was missed by some articles. Most of the early published review studies focused on phenotypic and molecule for identification of the fungal infection, but rarely on availability of molecular methods, so by proper awareness about availability of molecular methods and its use, the management of Mucormycosis and its mortality effects can be reduced.